The Role of the Government in the Development of Lodtunduh Tourism Village - Ni Wayan Gita Sadhana Savitri; Made Sera Septiani (Tourism and Hospitality Insights, 2025)
Introduction: The development of tourism villages has become a key strategy to improve community welfare and regional competitiveness, particularly in the post-Covid-19 era, which emphasizes quality and sustainable tourism. Lodtunduh Village in Gianyar Regency was designated a tourism village in 2019 due to its unique natural, cultural, and man-made attractions, as well as its strategic location as a buffer zone for the Ubud tourism area. However, its development still faces several challenges, including low human resource capacity, limited access to capital, weak networking, inadequate institutional management, and suboptimal promotion. Methods: This study employs a qualitative approach with data collected through observation, in-depth interviews with stakeholders, and literature review. The data were analyzed using NVivo software to identify key themes related to the role of government in tourism village development. Results: The findings show that the government plays a strategic role in four main aspects: (1) community capacity building, (2) formulation of regulations and designation of tourism village status, (3) promotion of tourism potentials, and (4) provision of financial support through village fund allocations. Conclusion: The active involvement of both local and village governments is proven to be a determining factor in fostering a participatory and sustainable development of Lodtunduh Tourism Village. Cross-sectoral synergy and the strengthening of local institutions are essential prerequisites to realize a tourism village that delivers long-term economic, social, and cultural benefits for the local community.